Radioactive Beams in Particle Therapy: Past, Present, and Future - Durante, Marco; Parodi, Katia (Frontiers in Physics, 2020)
Heavy ion therapy can deliver high doses with high precision. However, image guidance is needed to reduce range uncertainty. Radioactive ions are potentially ideal projectiles for radiotherapy because their decay can be used to visualize the beam. Positron-emitting ions that can be visualized with PET imaging were already studied for therapy application during the pilot therapy project at the Lawrence Berkeley Laboratory, and later within the EULIMA EU project, the GSI therapy trial in Germany, MEDICIS at CERN, and at HIMAC in Japan. The results show that radioactive ion beams provide a large improvement in image quality and signal-to-noise ratio compared to stable ions. The main hindrance toward a clinical use of radioactive ions is their challenging production and the low intensities of the beams. New research projects are ongoing in Europe and Japan to assess the advantages of radioactive ion beams for therapy, to develop new detectors and to build sources of radioactive ions for medical synchrotrons.